2020
DOI: 10.1002/ana.25844
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulation Timing in Cardioembolic Stroke and Recurrent Event Risk

Abstract: Objective: Guidelines recommend initiating anticoagulation within 4 to 14 days after cardioembolic stroke. Data supporting this did not account for key factors potentially affecting the decision to initiate anticoagulation, such as infarct size, hemorrhagic transformation, or high-risk features on echocardiography. Methods: We pooled data from stroke registries of 8 comprehensive stroke centers across the United States. We included consecutive patients admitted with ischemic stroke and atrial fibrillation. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 25 publications
0
17
0
2
Order By: Relevance
“…According to more recent results from the ‘Initiation of Anticoagulation after Cardioembolic stroke’ (IAC) study (n = 1,289), however, no relevant differences in occurrence of ischaemic or haemorrhagic events were found when comparing the starting interval of 4–14 days with earlier or later administration of anticoagulation. 16 In accordance, neither the ‘Clinical relevance of Microbleeds in Stroke’ (CROMIS-2) study 24 (n = 1,355) showed a difference between an early (≤ 4d) or later (> 4d) start of anticoagulation in regard to outcome measures, nor did the ‘Stroke Acute Management with Urgent Risk-factor Assessment and Improvement’ (SAMURAI-NVAF) study (n = 499; ≤ 3d vs. > 3d). 25 Other smaller studies were conducted yielding heterogeneous findings.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…According to more recent results from the ‘Initiation of Anticoagulation after Cardioembolic stroke’ (IAC) study (n = 1,289), however, no relevant differences in occurrence of ischaemic or haemorrhagic events were found when comparing the starting interval of 4–14 days with earlier or later administration of anticoagulation. 16 In accordance, neither the ‘Clinical relevance of Microbleeds in Stroke’ (CROMIS-2) study 24 (n = 1,355) showed a difference between an early (≤ 4d) or later (> 4d) start of anticoagulation in regard to outcome measures, nor did the ‘Stroke Acute Management with Urgent Risk-factor Assessment and Improvement’ (SAMURAI-NVAF) study (n = 499; ≤ 3d vs. > 3d). 25 Other smaller studies were conducted yielding heterogeneous findings.…”
Section: Discussionmentioning
confidence: 97%
“… 15 However, this finding could not be confirmed in a more recent study. 16 Previous studies are limited by sample size, confounding and especially confounding by indication. Therefore, the recommendations for the ideal timing of anticoagulation after acute IS are still conflicting.…”
Section: Introductionmentioning
confidence: 99%
“…Several observational studies have also reported outcomes according to anticoagulation timing (Supplementary Table 1). Collectively, these studies suggest that early anticoagulation with a NOAC is not associated with a high risk of intracranial haemorrhage, and that this risk is low compared to that of recurrent ischaemic stroke (77)(78)(79)(80)(81)(82)(83). Unexpectedly, several studies of these studies found numerically higher intracranial haemorrhage rates with more delayed anticoagulation, or similar or higher rates of recurrent ischaemia in early treatment groups (80)(81)(82)(83).…”
Section: Current Evidencementioning
confidence: 95%
“…Collectively, these studies suggest that early anticoagulation with a NOAC is not associated with a high risk of intracranial haemorrhage, and that this risk is low compared to that of recurrent ischaemic stroke (77)(78)(79)(80)(81)(82)(83). Unexpectedly, several studies of these studies found numerically higher intracranial haemorrhage rates with more delayed anticoagulation, or similar or higher rates of recurrent ischaemia in early treatment groups (80)(81)(82)(83). Given substantial imbalances in stroke severity, size and the presence of haemorrhagic transformation between groups, these results are likely to be confounded by treatment bias.…”
Section: Current Evidencementioning
confidence: 99%
“…They recommend to start anticoagulation within 3-4 days after mild and small strokes (<1.5 cm), after 7 days for moderate and after 14 days for large strokes. The aforementioned approaches have been tested in observational studies with inherent limitations [19]. Most recently, first results of the TIMING trial (NCT02961348; Sweden) were presented at the 7th European Stroke Conference (ESOC) 2021.…”
Section: Introductionmentioning
confidence: 99%